PEMBERDAYAAN KELOMPOK TANI DALAM PROGRAM KETAHANAN PANGAN DI DESA WATOONE, KABUPATEN FLORES TIMUR - Tokan, Frans Bapa; Lamawuran, Yosef Dionisius; Bidi, Maximianus Ardon (Universitas Padjadjaran, 2025)
Law No. 6 of 2014 concerning Villages emphasizes the central government’s extensive promotion of strengthening the capacity of human resources in villages through village fund schemes for empowerment. However, village governments for various reasons, tend to focus more on village infrastructure development over human resource empowerment, resulting in stagnant human resources in villages. The limited knowledge and skills of farmer groups have led to restricted access to community empowerment programs. This community service activity (PkM) aims to enhance the critical awareness of farmer groups to gain access to justice for village development programs and acquire agricultural technology skills for dryland farming through sustainable empowerment. The Participatory Rural Appraisal (PRA) approach is employed as a solution to empower farmer groups in addressing the problems they encounter. Through this PkM, which focuses on enhancing critical awareness and empowerment in the field of food security, farmer groups have become more confident in voicing their own aspirations, demanding access to justice to obtain assistance in the skills of using agricultural technology to increase their agricultural production.Undang-undang No. 6 Tahun 2014 tentang Desa menegaskan bahwa, pemerintah pusat secara masif mempromosikan penguatan kapasitas sumber daya manusia di desa melalui skema dana desa untuk bidang pemberdayaan. Namun pemerintah desa dengan berbagai alasan lebih fokus pada pembangunan infrastruktur desa dan hasilnya SDM di desa tetap berjalan di tempat. Minimnya tingkat pengetahuan dan ketrampilan kelompok tani telah berdampak pada rendahnya akses terhadap program pemberdayaan masyarakat. Kegiatan PkM ini bertujuan meningkatkan kesadaran kritis kelompok tani memperoleh akses keadilan terhadap program pembangunan desa dan penguasaan teknologi pertanian pada lahan kering melalui pemberdayaan secara berkelanjutan. Pendekatan